Identidades polinomiais com involução de álgebras de incidência - Ewerton da Silva Lemes (2016)
In this work we study polynomial identities with an involution in an incidence algebra I(P, F ) where P is a connected locally finite poset with an involution ? whose largest chain has, at most, 3 elements, and F is a field of characteristic zero. We determine the involutions and automorphisms of the crown C2n, its equivalent involutions as well and, from that, we classify the involutions on I(C2n, F ) by determining its equivalence classes